ANALYSIS OF MARKETPLACE USAGE AND PAYLATER FEATURES EFFECT ON CONSUMPTIVE BEHAVIOR OF LP3I MEDAN POLYTECHNIC STUDENTS - Muharsyah Hafiz; Asmaul Husna; Mayang Murni; Ika Sari Dewi (SEAN Institute, 2023)
The development of communication technology, media, and global infrastructure has an impact on various sectors such as the trade industry, government, social, and political issues. In the trade industry sector, the pattern of business activities has evolved from direct trade to indirect trade through various available marketplace platforms. However, technological developments also make payments easier by utilizing the PayLater feature. Even if you do not have enough money, you can use the paylater feature to purchase the items you want. Based on the convenience offered, another effect is increased consumer behavior, when a person has excessive, irrational need. The data used is primary data collected from questionnaires distributed to Medan LP3I Polytechnic students at the Medan Baru and Medan Marelan campuses. The results show that both partially and simultaneously, the marketplace and paylater variables have no effect on consumptive behavior.